A Comparative Analysis of Golestan and rhymed Prose on the basis of Arabic Rhetoric - Taher Lavzheh; Rahim Kooshesh; Abdoolah Toloueiazar (Literary Arts, 2015)
Abstract Harmonious and rhymed prose is a literary kind of speech characterized by producing music and intonation in order to conveying meaning of the context as well as possible and influencing the addressee more. In this paper main question is âwhether Saâdi in writing the Golestan, besides of applying rules of this kind of speech in Persian language, has used those characteristics of rhymed prose that exist in the main Arabic rhetoric books?â For this purpose, Characteristics of rhythmic and rhymed prose in Arabic rhetoric books have been examined by using description-annalistic approach, and brief pointing to the situation of Persian rhetoric science. The hypothesis is based on the belief that Golistanâs author uses ideas of Arab rhetorician in composition of this book to strengthen the structure of Harmonious and rhymed prose. The aim of the present study is recognizing that Sa'di in the rhymed prose of Golistan how much has used important Arabic rhetorical resources in the field of word and meaning. Having a critical look at the rhetorical books, New and Old Persian sources, it can be found that the researchers noted only a short definition limited to interpretation of some words or expressions based on great prose works and poetries, and not expressed their opinion by a critical attitude and also not looked on the details exactly and thoroughly of the aesthetic view. In the other side, in Arabic literature up to the Saâdiâs range, the field of rhetoric has been expanded and developed more and more. Most parts of Golistan are consistent with theories in view of Arab rhetoricians that in the following of this paper some cases are briefly mentioned: In the period of Abuhelal Askari, main idea was that meaning is superior to the word, and meaning was not as important as word. Abd ol-Qahr Jorjani abolished that belief and so emphasized that word and meaning cannot be separated and also proved that word out of the meaning frame and context order could have no sense, so that, be attributed to rhetoric. According to Ibn Asir, rhyme has its own rules and standards. So, it is not merely coming two uniformed or symmetrically matched parts of speech. But it is necessary that the harmony and consonance be embedded in its best state and appropriate demanded place in the speech. Ibn Asir and other great Arab rhetoricians know some conditions necessary for applying harmonious and rhymed prose and suggest the authors use them: 1- Appropriate words in speech should be chosen 2- The combination of words in sentences be at best 3- It is not correct that meaning follows the word 4- Each parts of rhythmic and rhymed prose should have different implications 5- Both parts of rhythmic and rhymed prose should be equal 6- No part should be longer or shorter than the other Those characteristics in Golistan are obviously represented. In writing most parts of Golistan, being free from artificiality is taken into account by the author. Beautiful words, poetic compounds with bluntly eloquent rhetoric, rhetoric in sense, strong cohesion and creating consistency in the whole work, are due to Sadiâs efforts to comply with those characteristics and features in the language and expression. So as the words and expressions are without cacophony, complexity, figuration, and other negative characteristics of literary speech. In Saâdies expression,Â  meaning follows the word. If a sentence is complete in meaning and does not need to be figured, it comes in the same simple form. In harmonious and rhymed prose of Golistan, there are examples of literary symmetry that both of sides have the same meaning and are not according to the conditions of harmony in the view of Ibn Asir and other Arab rhetoricians. But it should be mentioned that in the artistic features of Persian language, literary repetition is pleasing and acceptable in the customary of rhetoric, and also circumlocution in harmonic and rhymed prose emphasizes the meaning to influence the audience. Based on what was presented in the context of this study, the following points may be noted as a result of discussions: Persian books of rhetoric up to Sadiâs time, havenât noticed to the artistic feature of consonance and harmony in prose, and rhetoricians have not tried to criticize its aesthetical aspects. So there is no doubt that Saâdi has been influenced by Arabic rhetoric that has made good criticisms on that. Saâdi has an artistic, creative and literary view about harmonious and rhymed prose and it is based on poetic and rhetoric scales of Qoran and Abuhelal Askari theories of âWord eloquenceâ and other rhetoricians, and Abd ol-Qaher Jorjaniâs âHarmony of Wordâ. Making use of harmonious and rhymed prose in most parts of Golistan, Saâdi has aimed at conveying the meaning to the audience as well as possible through this kind of literary discourse. So the audience not only understands the artistic massage but also becomes familiar with music of words and their image making power, and therefore feels satisfaction more than before. Also Saâdi against the Arabs rhetoriciansâ claims, in some cases proves that while observing the artistic aspects of consonance, this literary figure can be applied contrary to their views